Epidemiology of Methicillin-resistant Staphylococcus aureus Colonization in Neonates within Neonatal Intensive Care Units: A Systematic Review and Meta-analysis - Seraphine Nkie Esemu; Arnol Bowo-Ngandji; Roland Ndip Ndip; Jane-Francis Tatah Kihla Akoachere; Nene Kaah Keneh; Jean Thierry Ebogo-Belobo; Cyprien Kengne-Ndé; Donatien Serge Mbaga; Nicholas Tendongfor; Hortense Kamga Gonsu; Jean Paul Assam Assam; Lucy Mande Ndip (Journal of Global Infectious Diseases)
Introduction: Methicillin-resistant Staphylococcus aureus (MRSA) colonization in neonatal intensive care units (NICUs) is a significant global health concern, leading to severe infections, extended hospital stays, and substantial economic burdens on health-care systems. To develop effective infection control strategies, we need to fill existing gaps in our understanding of MRSA epidemiology in neonates. The aim of this systematic review is to provide an extensive analysis of the proportion of MRSA colonizations in NICUs. Methods: We used a comprehensive search strategy across databases such as Medline, Embase, Global Health, Web of Science, and Global Index Medicus, in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Articles were independently reviewed and selected based on a variety of criteria, including the inclusion of neonates tested for MRSA colonization during NICU stay, and the reporting of community-acquired and hospital-acquired MRSA (CA-MRSA and HA-MRSA) incidence levels. Exclusion criteria included studies outside NICUs, those focused on specific MRSA outbreaks or clinical infections, review studies, and those lacking abstracts or full texts. Five authors independently extracted data, which was summarized and checked for quality. Statistical analysis included a random-effects model to compute pooled proportions, stratification by geographical location, evaluation of heterogeneity, and examination of publication bias. Results: Our systematic review evaluated 62 studies out of an initial 536 records identified. The majority of the selected studies were conducted in high-income countries, primarily in the United States. From these studies, we estimated a cumulative incidence rate of 7.2% for MRSA colonization in NICUs. When the source of MRSA was considered, CA-MRSA incidence was 2.7%, while HA-MRSA incidence was notably higher at 11%. A subgroup analysis showed geographical differences in the cumulative incidence of MRSA colonization in NICUs, with Brazil having the lowest incidence and Taiwan the highest. The proportion of HA-MRSA colonization also varied significantly by country, with South Korea reporting higher incidence rates than the United States. However, the differences in CA-MRSA colonization rates between countries and WHO regions were not statistically significant. Conclusions: Our systematic review found a cumulative incidence of 7.2% for MRSA colonization in NICUs, with HA-MRSA (11%) being more prevalent than CA-MRSA (2.7%). Regional variations were detected, with Taiwan exhibiting the highest cumulative incidence and South Korea having both the highest CA-MRSA and HA-MRSA. These findings underline the substantial public health impact of MRSA, especially in NICUs, necessitating context-specific prevention and control strategies. Future research should strive to address these regional disparities and aspire to attain a more globally representative understanding of MRSA colonization rates.